THE ROLE OF COMMUNICATION IN ENHANCING LEADERSHIP STYLES: CASE STUDIES FROM INDOMARET, ALFAMART, AND SALES TEAMS - Angga Haikal Wahyudi; Muhammad Zul’Asfy Rayhan, Gloria Salsa Br Sembiring, Bunga Nailah Syam, Ermelia Verawaty Hutagalung (Jurnal Komunikasi, 2025)
Effective communication is a cornerstone of successfulleadership, influencing organizational culture, employeemorale, and overall productivity. This journal exploresthe  role  of  communication  in  enhancing  variousleadership  styles,  focusing  on  case  studies  fromIndomaret and Alfamart, two prominent retail chains inIndonesia,  along  with  insights  from  sales  teams.Through qualitative analysis, including interviews andobservations, this study examines how leaders at theseorganizations utilize communication strategies to fostercollaboration,    motivate    employees,    and    navigatechallenges.  The  findings  reveal  that  leaders  whoprioritize    transparent,    inclusive,    and    adaptivecommunication  not  only  enhance  their  leadershipeffectiveness    but    also    cultivate    a    positive    workenvironment    that    drives    team    performance.    Thisresearch  contributes  to  the  understanding  of  thedynamic    interplay    between    communication    andleadership,  offering  practical  recommendations  forenhancing leadership practices in retail and beyond